ANTIâDIABETIC ACTIVITY OF SAMBILOTO EXTRACT (Andrographis paniculata Ness) TO DECREASE BLOOD GLUCOSE LEVEL OF ALOXANâINDUCED DIABETIC RAT - Wartini, Sudarmi, Agustina Intan Niken Tari & (Proceeding of International Congress, 2014)
This research aimed to measure dosage of sambiloto (Andrographis paniculata Ness) extract to decreaseblood glucose level of diabetic rats (Rattus norvegicus). Completely randomized design was applied forexperiment in triplicate sampling and 7 treatments: D0, D1, D2 of normal, diabetic, and 0.9 mg glibenclamidecontrol, respectively; D3, D4, D5 of 100, 200, 400 mg sambiloto extract respectively; and D6 of 200mg sambiloto + 0.9 mg glibenclamide; all dosage in 200 g body weight basis of 2 months old male whiteWistar rats weigh Â± 200 g for 21 days. Anova and KruskalâWallis were used as statistic analysis; results thenfurtherly analyzed using Moods Median Test at Î± 5%. Results showed that sambiloto extract at dosage of100 mg, 200 mg, 400 mg/200 g body weight as well as combination of 200 mg sambiloto + 0.9 glibenclamideable to reduce rat blood glucose level. Interestingly, 400 mg sambiloto/200 g body weight was comparableto the result obtain using 0.9 mg glibenclamide/200 g body weight of 56%. While rats treated withcombination of 200 mg sambiloto + 0.9 mg glibenclamide/200 g body weight had 58% lower blood glucosecompare to initial blood glucose level, however hypoglycemic risk need to be considered.Keywords: antiâdiabetic, sambiloto extract, blood glucose level